ÅRHUS - Raahauge, Kirsten Marie (Tidsskriftet Antropologi, 2003)
From the point of view of inhabitants of Skåde Bakker and Fedet, two well-off neighbourhoods in the Danish city of Aarhus, this article discusses social and visual perceptions of space. The spatial understanding of the city of Aarhus is twofold: it is understood simultaneously as an entity (a coherent city with centre and periphery) and as an archipelago of different spatial organisations in a big urbanised sea. Among the multitude of spaces and spatial understanding the article deals with different categories such as the central district, the neighbourhoods of Skåde Bakker and Fedet, transit space and virtual space. The topic, space perceptions, is understood very concretely, as social and visual organisations of the relationship between form and space, and on its way through the town of the well off city dwellers the article describes gardens and landscapes as well as roads and shopping areas of Aarhus.